2006
DOI: 10.1007/s10552-005-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Spatial Scan Statistic to Identify Geographic Variations in Late Stage Colorectal Cancer in California (United States)

Abstract: Spatial scan analyses can complement descriptive statistics, but results must be interpreted with consideration of factors that affect the ability to detect meaningful differences such as the number of events observed, accuracy in geocoding rural versus urban addresses, and the difficulty of adjusting for covariates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…More than 1 million new cases of colorectal cancer are clinically diagnosed each year and more than 500,000 patients die from colorectal cancer annually (16). More than 20% of colorectal cancer cases are diagnosed at a late stage and this percentage is higher in developing countries (17). Thus, many patients experience recurrence after colorectal resection.…”
Section: Introductionmentioning
confidence: 99%
“…More than 1 million new cases of colorectal cancer are clinically diagnosed each year and more than 500,000 patients die from colorectal cancer annually (16). More than 20% of colorectal cancer cases are diagnosed at a late stage and this percentage is higher in developing countries (17). Thus, many patients experience recurrence after colorectal resection.…”
Section: Introductionmentioning
confidence: 99%
“…Another study (Pollack et al, 2006) in California showed 57% of overall cases of colorectal cancer were diagnosed at a late stage. Californians diagnosed with latestage colorectal cancer were more likely to be Hispanic and living in areas of lower socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using data from a single state or province have reported associations of a variety of patient characteristics with colorectal cancer stage at diagnosis, including age, sex, race/ethnicity, comorbid conditions, insurance status, socioeconomic status, smoking status, and distance to primary care provider [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Halpern et al [30] used data from the National Cancer Data Base (NCDB) to evaluate the association between insurance status, race/ethnicity, and stage at diagnosis for 12 sites of cancer, including colorectal cancer, for a large patient population across the US.…”
Section: Introductionmentioning
confidence: 99%